Diagnostic and therapeutic aspects of recurrent renal stone disease (duplicate) - Meyers, Anthony; Whalley, Natalie; Martins, Maria (African Journal of Nephrology, 2009)
This paper was originally published in Vol 2, No 1 (1998) and can be accessed via the archive. It was re-published, in error, in Vol 13, No 1 (2009).